Lithium-Ion Battery Cycling for Magnetism Control - Zhang, Qingyun; Luo, Xi; Wang, Luning; Zhang, Lifang; Khalid, Bilal; Gong, Jianghong; Wu, Hui (Nano letters, 2016)
Magnetization and electric-field coupling is fundamentally interesting and important. Specifically, current- or voltage-driven magnetization switching at room temperature is highly desirable from scientific and technological viewpoints. Herein, we demonstrate that magnetization can be controlled via the discharge–charge cycling of a lithium-ion battery (LIB) with rationally designed electrode nanomaterials. Reversible manipulation of magnetism over 3 orders of magnitude was achieved by controlling the lithiation/delithiation of a nanoscale α-Fe2O3-based electrode. The process was completed rapidly under room-temperature conditions. Our results indicate that in addition to energy storage LIBs, which have been under continuous development for several decades, provide exciting opportunities for the multireversible magnetization of magnetic fields.